Somaesthetic Design - Arnold Mages, Michael; Neely, Stephen (transcript Verlag, 2026)
Over the past twenty-five years, design practice has expanded from making objects to shaping experiences that unfold in-time. As this expansion has accelerated, designers have gained powerful new tools – but often without a shared language for shaping embodied experience. Somaesthetic Design: The Experiencing Body and the Dynamics of Time responds by focusing on the experiencing body as a key source of design knowledge. Drawing from embodied practices and performance traditions, Michael Arnold Mages and Stephen Neely give designers a shared vocabulary and framework for understanding, crafting, and evaluating lived experience as it is felt and sustained in time.